ANALISIS TINGKAT EFISIENSI TEKNIS DALAM USAHATANI PADI DENGAN FUNGSI PRODUKSI FRONTIR STOKASTIK - Ahmad Muslim (Universitas Islam Indonesia, 2008)
The growth of productivity (yield) will be the major source of rice production in the next some few years to come. However, the development of rice productivity is facing the limited government budgets and the continuation of the conversion of land function. Therefore, the rice farming need to be conducted more efficiently. It means that the management skills of farmers need to be improved. The objective of the study is to estimate the levels of efficiency of rice farming in Kediri and Nganjuk of East Java Province and to see its distribution among farmers, using stochastic frontier production function. The results of the study are expected to help the policy makers in designing and improving the agricultural extension strategy. Keywords: efficiency, productivity, stochastic frontier production function, management skills.